Protective effect of epicatechin in diabetic-induced peripheral neuropathy: A review - Jyoshna Rani Dash, Gurudutta Pattnaik, Goutam Ghosh, Goutam Rath, Biswakanth Kar (Journal of Applied Pharmaceutical Science, 2023)
Flavonoids are naturally occurring substances that can be found in plants and various foods and may have health benefits in the treatment of neuropathic pain; however human clinical data are still inadequate. Because of their anti-oxidant characteristics, a plant-derived flavonoid known as epicatechin is widely employed in the treatment of diabetes and its consequences. Furthermore, epicatechin reduces the polyol pathway, the generation of advanced glycation end products, and oxidative stress and neuroinflammation, which are all associated with the advancement of neuropathy induced by diabetes. This review article presents an overview of the different pathology of diabetic neuropathy and the role of epicatechin to ameliorate neuropathic pain, which can be helpful in the management of microvascular complications of diabetes.